Pengaruh Kenaikan Harga Solar terhadap Usaha Penangkapan Nelayan di Pelabuhan Perikanan Nusantara Palabuhanratu, Sukabumi - Iis Diatin (Buletin Ekonomi Perikanan, 2003)
The government of Indonesia establish a policy to stabilize the fuel price according to the price fluctuation In global market by using Mid Oil Platts Singapore (MOPS) as a standard.The aim of this policy is to Improve fishermen financial capacity. One way to Implement this Is through provide gradual subsidy to the targeted fishermen. The government increases fuel price every month since January until December 2002. This condition promotes positive Impacts to all sectors, Include fisheries specially fish catch Industry. This fishing activity Is a part of fisheries Industries which depend on fuel. Consequently, fisherman Income In PPN (National Asherles Port) Palabuhan Ratu decreases. On financial side, the industries that use vessel 5-10 GT are not suitable If fuel price Increases until 36%.